Sex differences in motor unit behaviour: A review - Lulic-Kuryllo, T.; Inglis, J. G. (Journal of Electromyography and Kinesiology, 2022)
The lack of systematic investigations on sex-related differences in motor unit behaviour poses a challenge in understanding and optimizing health and performance in males and females. Limited investigations revealed that sex differences in motor unit behaviour might be present in human muscles. This review summarizes the current knowledge on sex differences in motor unit behaviour and potential factors that may contribute to these differences. We show significant under-representation of female participants in motor unit studies and a limited number of studies investigating sex differences in motor unit behaviour. We place the current insights within the context of methodological limitations and outline several recommendations and future directions to improve female representation in this research area. We conclude that there is an urgent need to gather more data in females and investigate sex differences in motor unit behaviour. The knowledge gained could be used to develop sex-specific approaches to improve neuromuscular performance and rehabilitation.